การวิเคราะห์ไอเอสเอสอาร์ของเปล้าใหญ่ Croton oblongifolius ในประเทศไทย - อรวรรณ ชลวาณิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Inter simple sequence repeats (ISSRs) technique is a PCR based method for amplification of DNA segment between two microsatellite repeats regions. Due to this technique has high reproducibility and polymorphism, ISSRs was employed to study genetic diversity of Croton oblongifolius (Plao-Yai) in Thailand. One-hundred and fifteen accessions of Plao-Yai were sampled in this study. Three SSR primers, G(GA)[subscript 7]GT, CRN[subscript 2](CTT)[subscript 2] and BSC(GA)[subscript 8], generated 213 bands. Phylogram from three primers revealed that 115 accessions of Plao-Yai have identified to 83 DNA patterns and classified as 2 major groups. The results of ISSRs showed high polymorphism within Croton oblongifolius species. The relationship of DNA patterns and chemical constituents from bark of Plao-Yai were studied using [superscript 1]H-NMR and TLC technique. Plao-Yai with different DNA patterns had different major chemical constituents. Plao-Yai with same DNA patterns had same chemical constituents. Therefor, chemical constituent data were concordant with DNA patterns